Pengembangan Instrumen Penilaian Tes Tertulis Bentuk Eksposisi Berbasis Hots Pada Pelajaran PKN - Qomariyah, Ryzca Siti; Megawati, Megawati; Putri, Rizka Amelia; Alhamni, Vega Fakis (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
Assessment is a series of the most important in learning. Assessment also provides objective feedback on what students have learned and is used to determine the effectiveness of learning. The research method is a guide for researchers about how to carry out research steps that are used to find, prove and various information or results that have been obtained from observations. This study uses qualitative and quantitative research models to analyze the questions. If the questions are analyzed qualitatively, this is done by examining aspects of the validity of the validation form, the aspects of which are: Material, Structure and Language. From the results of research activities at Ketopen Elementary School regarding written tests. The group got very satisfying results, because we got a lot of insight about the written test in detail starting from the definition, function of the test, examples of written tests and even how to make written test questions. From some of the results of group interviews with teachers at SDN Ketompen, the next step is for the group to compose questions in the form of HOTS-based descriptions in science learning for class VI. Written in the form of a description is a question that contains questions, where the questions are answered by expressing the thoughts of the test takers. So the way to make HOTS and LOTS questions is guided by the bloom taxonomy in which there are indicators and division of cognitive levels which are complemented by operational verbs starting from C1 to C6 where levels C1, C2, and C3 are the lost question categories. and starting at level C4, C5 and C6, it means the HOTS question category.